Body mass index in midlife and dementia: Systematic review and meta‐regression analysis of 589, 649 men and women followed in longitudinal studies. Issue 1 (20th June 2017) - Albanese, Emiliano; Launer, Lenore J.; Egger, Matthias; Prince, Martin J.; Giannakopoulos, Panteleimon; Wolters, Frank J.; Egan, Kieren
Abstract: Introduction: We conducted a meta‐analysis of the conflicting epidemiologic evidence on the association between midlife body mass index (BMI) and dementia. Methods: We searched standard databases to identify prospective, population‐based studies of dementia risk by midlife underweight, overweight, and obesity. We performed random‐effects meta‐analyses and meta‐regressions of adjusted relative risk (RR) estimates and formally explored between‐study heterogeneity. Results: We included 19 studies on 589, 649 participants (2040 incident dementia cases) followed up for up to 42 years. Midlife (age 35 to 65 years) obesity (BMI ≥ 30) (RR, 1.33; 95% confidence interval [CI], 1.08–1.63), but not overweight (25 < BMI < 30) (RR, 1.07; 95% CI, 0.96–1.20), was associated with dementia in late life. The association with midlife underweight (RR, 1.39; 95% CI, 1.13–1.70) was potentially driven by residual confounding ( P from meta‐regression = .004), selection ( P  = .046), and information bias ( P  = .007). Discussion: Obesity in midlife increases the risk of dementia. The association between underweight and dementia remains controversial.